Upaya Pencegahan dan Pengendalian Demam Berdarah Dengue dalam Bentuk Peta Tematik di Kecamatan Rappocini - Wulandhani, Suci; Purnamasari, A. Bida; Syam Pratomo, Ryan Humardani (Fakultas MIPA UNM, 2018)
Abstract. Dengue hemorrhagic fever (DHF) is a disease caused by dengue virus infection. One symptom of dengue virus infection is high fever and headache. Dengue virus is a virus from the genus Flavivirus, family of Flaviviridae. This dengue fever is a dangerous viral disease because it can cause sufferers to die in a very short time / several days. The existence and population density are often associated with transmission, endemicity and Extraordinary Events (EE) of DHF. Disease mapping by utilizing digital technology to support epidemiological investigations and also as a tool to monitor regional conditions for dengue disease. The purpose of this study was to determine efforts to prevent and control dengue disease by mapping. The results of the study show that mapping can be seen as increasing and decreasing the number of cases of dengue disease so that it can assist in data management and reporting of information to monitor areas at risk of contracting dengue disease. Suggestions given need to do further research using other variables that are the cause of the high rate of dengue cases, so that it can be utilized by related agencies as the basis of the information system supporting the decision on preventive measures to combat dengue. Keywords: prevention and control, DHF, mapping.